Simulation of Hydrogen Combustion Characteristics in Argon-Oxygen Compression Ignition Engine using Large Eddy Simulation (LES) Turbulence Model. (October 2019) - Nasruldin, Muhammad Arif Arsyad; Mansor, Mohd Radzi Abu
Abstract: Hydrogen combustion in a noble gas atmosphere will increase thermal efficiency because of higher specific heat ratio. During the compression stroke, noble gas produces a higher temperature at the same compression ratio compared to standard air compression. Argon is the best noble gas in this study because it is abundant and readily available. In this study, argon replaced the nitrogen and formed the argon-oxygen atmosphere in a compression ignition engine. The objectives of this study are to determine the suitable initial temperature for simulation work based on the experimental value and to study the effect of injection parameter changes towards combustion and emission characteristics. This study uses Converge V2.4 CFD simulation based on Yanmar NF19SK engine parameter. The turbulence model used Large Eddy Simulation (LES) due to accessibility in extensive eddies calculation that has a significant fraction of energy. Thus, combustion analysis accuracy also increased. Base grid of 5mm with adaptive mesh refinement (AMR) and fix embedding is chosen based on simulation time and computer storage. Combustion simulations involve changing of initial temperature, the start of injection (SOI) and injection pressure to obtain pressure and heat release rate data. At intake temperature of 370K, hydrogen combustion shows the highest peak pressure, and for intake temperature at 500K, SOI of 700 °CA produces the highest peak pressure for the combustion. Ignition delay increases as the temperature and injection pressure decrease.